Street art commodification and (an)aesthetic policies on the outskirts of Lisbon - Raposo, O. (2022)
In this article, I discuss how street art has become an ally of urban policies molded by the creative city paradigm in marginalized neighborhoods of Lisbon (Portugal). Based on a dense ethnography of a peripheral neighborhood of this Southern European city, I follow the trail left by how public power uses the commodification of street art as an instrument for urban regeneration, touristification, and management of inequalities. The different meanings and interests around this policy are examined in street art festivals and tours, focused on the participation of young people as local guides. This urban policy has changed the negative public image of the neighborhood, with street art being combined with a multicultural experience commodified in guided tours for tourists. However, by ignoring the opinions of the residents on the interventions, this policy follows a top-down approach in which street art aesthetics operate as a device of subjugation and maintenance of the subaltern, beautifying processes of exclusion.